PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MEGA FINANCE CABANG KANDIS KABUPATEN SIAK - Anuar, Saiful (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
The purpose of this study was to determine the influence of work discipline on employee performance at PT. Mega Finance Cabang Kandis Kabupaten Siak. The sample in this research is all employee at PT. Mega Finance Cabang Kandis Kabupaten Siak which amounts to 45 people. Sampling was conducted using a sample of saturated (Sugiyono, 2010:96)